Cross-Sectional study of differences in phenomenology of acute psychosis with or without cannabis - Pal, V. S.; Rastogi, Pali; Chauhan, Amrita; Niranjan, Vijay (International Journal of Medical Research and Review, 2017)
Background: Therehas been plethora of research regarding cannabis use disorder but very few studiesreporteddemographicand phenomenological differences of acute psychosis with cannabis use to those of acute psychosis without cannabis use. This study attempted to evaluate the demographic and phenomenology differences between two groups of patients presenting with acute psychosis with cannabis use and acute psychosis without cannabis use. Material & Method: Two group of patients recruited for study were ‘Cases with Cannabis’ and ‘control without Cannabis’ presenting with acute psychosis with preceding cannabis use and second one presenting with acute psychosis without preceding cannabis use in out-patient department of psychiatry, M. Yhospital, Indore Assessment done using rating scales. Results: Acute psychosis with cannabis wascharacterizedby primarily polymorphic clinical picture with predominance of positive and mood symptoms both in clear and disturbed sensorium.Acute psychosis without cannabis was characterized by mixed positive and negative symptoms in clear sensorium. In ‘Cases with cannabis’ group 96.7% were males and 3.3% were females, mean age was higher (33.7%) than control (27.7%) group. Conclusion: Acute psychosis with cannabis is characterized by primarily polymorphic clinical picture with predominance of positive and mood symptoms both in clear and disturbed sensorium. Acute psychosis without cannabis is characterized by mixed positive and negative symptoms. General symptoms of psychosis were also more in acute psychosis without cannabis.